1355 Clinical Profile of Congenital Heart Diseases in Children in Khartoum, Sudan. (12th October 2021) - Elhassan, A B E; Salman, M. Suliman T; Elkhidir, I. Hassan E; Mohamed, S. Omer O; Ibrahim, A; Mohammed, F; Abuzied, A; Elhassan, M
Abstract: Aim: Congenital heart diseases (CHDs) are heart abnormalities that present at birth and are one of the most common birth defects in children. Few studies assessed the clinical profile of CHDs in Sudan, and they are almost outdated. The aim of this study was to provide a recent overview of the clinical profile of CHDs in Khartoum, Sudan. Method: a descriptive cross-sectional hospital-based study was done in 2016 in 3 main pediatric tertiary care hospitals in Khartoum. Firstly, the authors included all patients presented with suspicion of cardiac diseases. From which only those diagnosed with CHDs were included. The total sample size was 112 patients, from which CHDs comprised 60 patients. Results: among the 112 patients, 53.6% had CHDs, 25% had acquired diseases, and 21.4% were normal. Of those with CHD, 60% were having acyanotic CHD, and 21.7% were having cyanotic CHD, the remaining patients had other cardiac defects. VSD was the most predominant individual CHD (33%), followed by ASD (19%), PDA (16.8%) and TOF (16.8%). VSD was the most common acyanotic lesion, while TOF was the most common cyanotic lesion followed by TGA and pulmonary atresia (PA). Conclusions: We have an updated overview of the clinical profile of CHDs in Khartoum, Sudan. CHDs were the most common form within all pediatric patients with cardiac disease. From these CHDs, acyanotic lesions were the most common ones. VSD was the most common acyanotic lesion followed by PDA. TOF was the most common cyanotic lesion. These findings are consistent with studies done regionally and internationally.